Cognitive Reappraisal Impairments in Positive Emotion Regulation Among Internet Addicts: Reduced Effective Connectivity From dlPFC to vmPFC. - Guo, Wenxin; Zhang, Wei (Scandinavian Journal of Psychology, 2026)
Internet addiction (IA) negatively impacts individuals' emotional regulation. However, previous studies have mostly focused on negative emotion regulation, neglecting the importance of regulating positive emotions. Internet addicts are more prone to emotional fluctuations following positive emotions, and elevated positive affect is a risk factor for mania and risky behaviors. Therefore, it is crucial to focus on the core deficits in positive emotion regulation among internet addicts, especially providing neural evidence to serve as targets for interventions. This study adopted a 2 (group: IA group; health control group) × 2 (emotion regulation condition: no emotional regulation; emotional regulation) × 2 (emotion regulation strategy: cognitive reappraisal and expression suppression) mixed experimental design. A total of 49 participants were included in the experiment (IA group: 22 participants; health control group: 27 participants). fNIRS was used to detect brain activity during emotional regulation. The results revealed that compared to the control group, internet addicts performed worse in regulating positive emotions, with lower activation in the dlPFC and a significantly reduced emotional regulation effect in the cognitive reappraisal condition, characterized by decreased effective connectivity from dlPFC to vmPFC. The effective connectivity between dlPFC and vmPFC plays a mediating role in the impact of internet addiction on emotion regulation. This study provides a reference for future interventions aimed at emotional issues in internet addicts, emphasizing the need to help maintain stable and balanced emotional states, focusing on enhancing cognitive reappraisal abilities and targeting the dlPFC and vmPFC for neural interventions. Keypoints: Internet addicts exhibited poorer performance to regulate positive emotions than control group.Reduced effective connectivity between dlPFC and vmPFC is a key neural indicator of cognitive reappraisal impairments in Internet addicts.It is crucial not only to reduce negative emotions among Internet addicts but also to help them maintain a stable and balanced emotional state.